2009
DOI: 10.1007/s00534-009-0049-y
|View full text |Cite
|
Sign up to set email alerts
|

Rat islet culture in serum-free medium containing silk protein sericin

Abstract: Serum-free medium containing sericin appears to be useful for islet culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…Morikawa et al [123] used sericin or FBS (fetal bovine serum) as medium for rat islets culture and there were no observed significant differences in survival and insulin secretion for 14 days. Ogawa et al [83] tested the effect of sericin and FBS on islet cell survival and insulin production and, compared to Morikawa et al [123], on the 12th day, all islets were morphologically intact in FBS culture, while only 50% were intact in sericin culture.…”
Section: Sericin Properties and Biomedical Applicationsmentioning
confidence: 99%
“…Morikawa et al [123] used sericin or FBS (fetal bovine serum) as medium for rat islets culture and there were no observed significant differences in survival and insulin secretion for 14 days. Ogawa et al [83] tested the effect of sericin and FBS on islet cell survival and insulin production and, compared to Morikawa et al [123], on the 12th day, all islets were morphologically intact in FBS culture, while only 50% were intact in sericin culture.…”
Section: Sericin Properties and Biomedical Applicationsmentioning
confidence: 99%
“…In this study, the morphology of pancreatic islets was maintained during isolation by adding sericin to the isolation solution, and Morikawa et al (2009) and Ohnishi et al (2012) reported the maintenance of islets during culture and cryopreservation by the addition of sericin to culture medium and frozen liquid. The advantages of the addition of sericin during the isolation process and the use of sericin in cultures and cryopreservation in the preservation process could be to maintain the morphology of pancreatic islets and to increase the volume of transplantable pancreatic islets isolated from one donor.…”
Section: Discussionmentioning
confidence: 90%
“…There are numerous reports on the various qualities of sericin; it has anti-oxidant and anti-apoptotic properties, is protective against ultraviolet damage, can accelerate the proliferation of various cells, and provide cytoprotective effects (Sasaki et al 2000; Sato et al 2011; Takahashi et al 2003; Terada et al 2002; Zhaorigetu et al 2003, 2007). We previously performed culture preservation and cryopreservation of pancreatic islets to demonstrate the cytoprotective effect of sericin on pancreatic islets (Morikawa et al 2009; Ohnishi et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…이러한 세리신은 구조적으로 크게 α-세리신과 β-세리신으로 구분되며, 용해도는 α-세리신이 β-세리신보다 우수한 것으로 알려져 있다. 실크의 천연 단백질은 생체적합성 및 기계적 물성이 우 수하며, 항산화 (Hwang et al 2011), 보습 (Hwang, et al 2009), 미백 (Jo et al 2011(Jo et al , kato et al 1998, 항노화 (Kim et al 2012, Mondal et al 2007) 및 세포사멸억제 (Morikawa et al 2009, Ohnishi et al 2012)와 관련된 효과가 우수한 것으로 알려져 있다 (Prasong et al 2009). 누에를 이용한 생체소재의 개발은 매우 오래전부터 이 루어져 왔다.…”
unclassified